TRANSLATION QUALITY OF EXPRESSIVE SPEECH ACT IN THE NOVEL ENTITLED BREAKING DOWN (AWAL YANG BARU) WRITTEN BY STEPHENIE MEYER - Hari Nugraha (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2019)
AbstractTranslation of speech acts is an interesting activity considering the process of understanding the message in it, must be related to the context (speech situation). Speech acts are one part of language that is defined as actions that contain utterances. This study was written with the aim of analyzing the speech acts used in the novel entitled "strike" and the quality of the translation based on accuracy, readability and acceptance. The stages of research, including descriptive qualitative research, are data collection, data analysis, klasificating data, quesionaring data, and making conclusions based on data without making data generalizations. From this research found, 159 speech data were classified into 19 types of expressive speech acts. From the research, it claims that the novel, especially ekspresife speech act has been translated well, and it has high qualities of trasnlation based on terms of accuracy, acceptance, and readability. Key word; translation quality, ekspresive speech act, breaking down